2007
DOI: 10.1097/wnr.0b013e3280c1e2e7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term memory of cocaine-associated context: disruption and reinstatement

Abstract: Long-term memory of cocaine-associated context was established by conditioned place preference learning. After 1 week, exposure to context in the absence of cocaine (memory retrieval) was paired with one of the following treatments: saline, scopolamine (muscarinic acetylcholine receptor antagonist), dizocilpine (MK-801; noncompetitive N-methyl-D-aspartate antagonist) or D-cycloserine (partial N-methyl-D-aspartate agonist). In subsequent conditioned place preference tests, place preference was suppressed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 21 publications
6
84
2
Order By: Relevance
“…It has also been shown that pre-extinction DCS administration facilitated fear extinction, although extinguished fear was normally renewed, suggesting that the drug may modestly facilitate extinction learning, but does not destroy the potential for relapse (Woods & Bouton, 2006). Moreover, the current results contrast with previous research assessing the impact of DCS administered after extinction learning, which indicated enhanced extinction consolidation of different drug-seeking behaviors after intra-BLA or systemic DCS injections (Botreau et al, 2006;Kelley et al, 2007;Nic Dhonnchadha et al, 2009;Paolone et al, 2009;Thanos et al, 2009). Nevertheless, additional reports have also shown other inconsistencies in the capacity of DCS to enhance extinction consolidation.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…It has also been shown that pre-extinction DCS administration facilitated fear extinction, although extinguished fear was normally renewed, suggesting that the drug may modestly facilitate extinction learning, but does not destroy the potential for relapse (Woods & Bouton, 2006). Moreover, the current results contrast with previous research assessing the impact of DCS administered after extinction learning, which indicated enhanced extinction consolidation of different drug-seeking behaviors after intra-BLA or systemic DCS injections (Botreau et al, 2006;Kelley et al, 2007;Nic Dhonnchadha et al, 2009;Paolone et al, 2009;Thanos et al, 2009). Nevertheless, additional reports have also shown other inconsistencies in the capacity of DCS to enhance extinction consolidation.…”
Section: Discussioncontrasting
confidence: 56%
“…Recent research has reported the role of DCS in the extinction of learned behavior involving appetitive stimuli, such as drug-seeking behavior, suggesting that systemic administration of DCS facilitates the extinction consolidation of self-administration and conditioned place preference (CPP) associated to different drugs (Botreau, Paolone & Stewart, 2006;Kelley, Anderson & Itzhak, 2007;Nic Dhonnchadha et al, 2010;Paolone, Botreau & Stewart, 2009;Thanos, Bermeo, Wang & Volkow, 2009;Thanos, Bermeo, Wang & Volkow, 2011) and enhances the persistence of extinction (Groblewski, Lattal & Cunningham, 2009). In contrast to such reports, a recent study showed that pretreatment with systemic DCS prior to extinction training had no effect on the extinction and subsequent reinstatement of morphineinduced CPP (Lu, Wu, Zhang, Ai & Li, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In our hands, propranolol treatment resulted in a permanent retrieval deficit, as the CPP did not re-emerge after 14 days in a test for spontaneous recovery or after a priming injection of cocaine. This latter effect is remarkable, as cocaine has been shown to reliably induce reinstatement of a CPP after extinction (Kelley et al, 2007;Mantsch et al, 2010;Mueller and Stewart, 2000;RodriguezArias et al, 2009). Because the passage of time and cocaine itself did not reinstate the CPP, we conclude that retrieval of the original association between cocaine and the conditioning context was disrupted.…”
Section: Discussionmentioning
confidence: 99%
“…A priming injection of cocaine has been shown to reliably induce reinstatement of a CPP after extinction (Kelley et al, 2007;Mantsch et al, 2010;Mueller and Stewart, 2000;Rodriguez-Arias et al, 2009). Behaviorally, both propranolol treatment and extinction training abolish the expression of a CPP; hence, in experiment 5, we determined whether the retrieval deficit induced by propranolol would prevent reinstatement of a CPP to a priming injection of cocaine.…”
Section: Propranolol Protects Against Cocaine-induced Reinstatementmentioning
confidence: 99%
“…This provides a tool for measuring the motivational salience of the cue, independent of the psychomotor effects of the drug. In a slightly different paradigm, context-induced or contextual reinstatement examines the associative strength of the physical environment in mediating drug-seeking behavior [52,58,[60][61][62][63][64]. Here, animals undergo extinction training in an experimental apparatus that is contextually unique from the apparatus where self-administration was acquired.…”
Section: Cue-and Context-induced Reinstatement Of Drugseeking Behaviormentioning
confidence: 99%